A COMPARATIVE STUDY OF SPORTS AGGRESSION BETWEEN MALE AND FEMALE BOXING PLAYERS - Dr. Yuwraj Shrivastava1, Mr. Ankit R2, Dr. Agam Pratap Singh3, Mr. Kushagra Bairagi4 Mr. Arnav Gupta5 , (Chelonian Research Foundation, 2023)
In the current study, a sample of 73 boxers—men and women—was chosen. There are 73 male and female boxers in the sample. 35 boys and 38 girls, respectively, make up the male and female boxing teams that competed in the state of Tamil Nadu. Players of both sexes were chosen at random to serve as subjects. On average, male and female boxing players ranged from 18 to 25. Data will be gathered using a questionnaire created by Buss, A. H. & Perry, M.P. (1992) (Buss, 1992). It also demonstrates that there is a substantial difference between male and female boxers in terms of verbal hostility, with female boxers displaying a marginally greater mean of verbal aggression than male boxers. Consequently, the theory that there is a considerable difference between verbal violence in male and female boxers was confirmed in male boxers. The third element, rage, shows a substantial difference between male and female boxers, with female boxers often displaying slightly higher levels of anger than male boxers. The idea that there is a sizable difference between female and male boxers in hostile aggression is supported by the observation that male boxers appear to exhibit slightly stronger hostility when compared to those female boxers in the final aspect of aggression, hostility. The sports aggression of Tamil Nadu's male and female boxers is the subject of this comparative study. The study looks at four different aspects: Aggression in all forms—physical, verbal, angry, and hostile. Data analysis provides fascinating new information about the parallels and differences between male and female aggression levels. The results offer insightful knowledge that sports trainers, coaches, and policymakers may use to improve training methods and advance gender-inclusive practices in boxing. Keywords: Physical aggression, verbal aggression, anger, hostility, gender differences, training strategies, gender-inclusive practices, sports aggression, boxing players, male and female, comparative study